Insights into the effects of occupant behaviour lifestyles and building automation on building energy use. (December 2017) - Fabi, Valentina; Barthelmes, Verena M.; Schweiker, Marcel; Corgnati, Stefano P.
Abstract: In order to optimize building energy consumption, Member States will have to establish minimum efficiency requirements for systems, and promote the introduction of active control system in new constructions or major renovations. Energy saving, plant efficiency and environmental sustainability are also factors delineating smart buildings. Interestingly, occupant behaviour is known to be one of the key sources of uncertainty in the prediction of building energy use. The success of automation strategies is recognized to be dependent on how the occupants interact with the building. The present research describes the effect of different building occupants' lifestyles and building automation on a high performing building.